Trans-inclusive Sexual Health Questionnaire to Improve Human Immunodeficiency Virus/Sexually Transmitted Infection (STI) Care for Transgender Patients: Anatomic Site–Specific STI Prevalence and Screening. (20th May 2022) - Tordoff, Diana M; Dombrowski, Julia C; Ramchandani, Meena S; Barbee, Lindley A
Abstract: Background: In 2018, the municipal Sexual Health Clinic in Seattle, implemented trans-inclusive questions about sexual behavior, anatomy, gender-affirming surgeries, and sexually transmitted infection (STI) symptoms in the clinic's computer-assisted self-interview (CASI) to improve care for transgender and nonbinary (TNB) patients. Methods: We calculated test positivity, the proportion of TNB patient visits that received testing for human immunodeficiency virus (HIV); syphilis; pharyngeal, rectal, and urogenital gonorrhea (GC); and chlamydia (CT) before (5/2016–12/2018) and after (12/2018–2/2020) implementation of new CASI questions, and the proportion of asymptomatic patients who received anatomic site–specific screening based on reported exposures. Results: There were 434 TNB patients with 489 and 337 clinic visits during each period, respectively. Nonbinary patients assigned male at birth (AMAB) had the highest prevalence of GC (10% pharyngeal, 14% rectal, 12% urogenital). Transgender women, transgender men, and nonbinary people AMAB had a high prevalence of rectal CT (10%, 9%, and 13%, respectively) and syphilis (9%, 5%, and 8%). Asymptomatic transgender women, transgender men, and nonbinary patients AMAB were more likely to receive extragenital GC/CT screening compared with nonbinary patients assigned female at birth. After implementation of trans-inclusive questions, there was a 33% increase in the number of annual TNB patient visits but no statistically significant increase in HIV/STI testing among TNB patients. Conclusions: TNB people had a high prevalence of extragenital STIs and syphilis. Implementation of trans-inclusive medical history questions at a clinic that serves cisgender and transgender patients was feasible and important for improving the quality of affirming and inclusive sexual healthcare. Abstract : Transgender and nonbinary patients had a high prevalence of extragenital sexually transmitted infections and syphilis. Incorporating trans-inclusive medical history questions at a clinic that serves cisgender and transgender patients was feasible and important for expanding access to inclusive sexual healthcare.